Occupational Health and Safety and the Mobile Workforce: Insights From a Canadian Research Program. (November 2019) - Neis, Barbara; Lippel, Katherine
Globally, employment-related geographical mobility (mobility to and within work) is a pervasive aspect of work that has potential health and safety implications. As an introduction to this special issue, this article defines the mobile workforce as those who engage in complex/extended mobility to and within work encompassing >two hours daily, less frequent but more extended mobility between regions and countries, and mobility within work such as between work sites or in mobile workplaces. Focusing on the Canadian context, we discuss the challenges associated with developing a statistical profile for this diversely mobile workforce and provide an overview of articles in the special issue identifying key health and safety challenges associated with extended/complex employment-related geographical mobility. We estimate that up to 16 percent of Canada's employed labor force (including those commuting > one hour one-way, temporary residents with work permits, and transportation workers) engage in extended/complex mobility related to work.